Increased platelet activation in sleep apnea subjects with intermittent hypoxemia - Krieger, Ana C.; Anand, Ranjini; Hernandez-Rosa, Evelyn; Maidman, Allison; Milrad, Sara; DeGrazia, Miles Q.; Choi, Alexander J.; Oromendia, Clara; Marcus, Aaron J.; Drosopoulos, Joan H. F. (Sleep & breathing, 2020)
Purpose Obstructive sleep apnea (OSA) is independently associated with increased risk for stroke and other cardiovascular diseases. Since activated platelets play an important role in cardiovascular disease, the objective of this study was to determine whether platelet reactivity was altered in OSA subjects with intermittent nocturnal hypoxemia. Methods Thirty-one subjects, without hypertension or cardiovascular disease and not taking medication, participated in the study. Subjects were stratified based on OSA-related oxygen desaturation index (ODI) recorded during overnight polysomnography. Platelet reactivity to a broad panel of agonists (collagen, thrombin, protease-activated receptor1 hexapeptide, epinephrine, ADP) was measured by monitoring platelet aggregation and ATP secretion. Expression of platelet activation markers CD154 (CD40L) and CD62P (P-selectin) and platelet-monocyte aggregates (PMA) was quantified by flow cytometry. Results Epinephrine-induced platelet aggregation was substantially decreased in OSA subjects with significant intermittent hypoxemia (ODI ≥ 15) compared with subjects with milder hypoxemia levels (ODI < 15) (area under curve, p = 0.01). In addition, OSA subjects with ODI ≥ 15 exhibited decreased thrombin-induced platelet aggregation ( p = 0.02) and CD40L platelet surface expression ( p = 0.05). Platelet responses to the other agonists, CD62P platelet surface expression, and PMA levels were not significantly different between groups. Reduction in platelet responses to epinephrine and thrombin, and decreased CD40L surface marker expression in significant hypoxemic OSA individuals, is consistent with their platelets being in an activated state. Conclusions Increased platelet activation was present in otherwise healthy subjects with intermittent nocturnal hypoxemia due to underlying OSA. This prothrombotic milieu in the vasculature is likely a key contributing factor toward development of thrombosis and cardiovascular disease. Trial registration NCT00859950